Integrating â€œDaily Learn English Applicationâ€ to Teach Speaking Skill in EFL Classroom - Anugrah, Nina Julia; Sumardi, Sumardi; Supriyadi, Slamet (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2019)
The generation who is raised in the digital world has come to believe learning meant to be loud, colorful, and energetic. Teachers who want to reach out to this generation need to use media to grab attention. Teachers must be adaptive, which means that they must begin to believe that integrating technology is an effective way of teaching. This research is aimed at investigating teacherâ€™s belief and practice on the integration of â€œDaily Learn Englishâ€ Application to teach speaking skill in EFL classroom. To reach the objective, a case study on an individual teacher was used in this research. Data collection techniques of the research were Interview and observation. The result indicated that the teacher believes that integrating